FRI0236 Structure and function of the fibrin network in patients with churg-strauss syndrome. (23rd January 2014) - Krawiec, P.; Batko, B.; Iwaniec, T.; Tłustochowicz, W.; Mastalerz, L.; Undas, A.
Abstract : Background: Churg-Strauss syndrome is a rare systemic necrotizing vasculitis, characterized by severe asthma, blood eosinophilia and eosynophilic infiltration of tissue. In the course of the disease thromboembolic incidence has been reported. Depending on the study the incidence of arterial occlusion ranging between 3.1-18.7% and a prevalence of venous occlusion between 5.8-30%. Objectives: We want to test the hypothesis that fibrin structure/function is unfavourably altered in patients with Churg-Strauss syndrome, which could be a novel prothrombotic mechanism tha operates in this disease. Methods: Ex vivo plasma fibrin permeability, turbidimetry and efficiency of fibrinolysis were investigated in 35 patients with CCS free of history of thrombotic events (24 female, 11 male, aged 48 [range, 21-80] years. The control group comprised 35 age- and sex-matched healthy volunteers. All patients were in stable phase of the disease. Results: Compared with controls, patients with CCS were characterized by significantly lower clot permeability (p<0.0001) indicating pores of smaller size in the fibrin network, shorter lag phase (p<0.0001) indicating quicker formation of fibrin clot, greater maximum clot absorbancy (p<0.0001) indicating thicker fibrin fibres and prolonged clot lysis time (p<0.0001). Fibrinogen (r=-0.55, p=0.0007), interleukin-6 (r=-0.37, p=0.0283) but not C-reactive protein (r=-0.12, p=0.5075) was inversely correlated with clot permeability and positively with clot lysis time (r 0.44 to 0.48; all p<0.02). Interestingly, both IgE and eosinophilia were inversely correlated (r -0.39 to -0.48; p<0.02) with clot permeability and positively associated (r 0.36 and 0.35; p<0.05) with clot lysis. Conclusions: This study is the first to show that Churg-Strauss syndrome is associated with unfavorably altered plasma fibrin clot phenotype, including resistance to fibrinolysis, which represents a novel prothrombotic mechanism that operates in this disease. Disclosure of Interest: None Declared